Online Meaningful Mathematics Learning Integrated by "Pintar tuntang Harati" in the New Normal Era - Suci Amalia Pebrianti; Agustin Dewanti Putri (Pancaran Pendidikan, 2020)
The 2013 curriculum focuses on achieving core competencies in attitudes, knowledge, and skills. The learning process which was replaced with online learning as a result of the COVID-19 pandemic does not mean eliminating the achievement of core competencies, especially attitude competencies. The positive attitude mandated by the 2013 curriculum is in the philosophy of Education in the Dayak tribe of Central Kalimantan, namely "Pintar tuntang Harati". The purpose of this scientific work is to provide a solution by first describing specifically the implementation of online learning in one of the Kotawaringin Timur district schools that are included in the co-pandemic red zone area in Central Kalimantan and student responses to online learning. The results of this study indicate that online learning has not fully integrated attitude core competencies. Attitude competencies can be achieved in online learning by making mathematics learning meaningful. The integration of meaningful mathematics learning with the attitude of "pintar tuntang harati" can go through three stages. This stage is to make learning close to students, learning not limited to online applications, and teachers as role models.